Exploring Global Research Trends on Extension Advisory Services in Climate-Smart Agriculture - PATHIKALAYIL RAJESH ANURANJ; SREERAM VISHNU (Indian Journal of Extension Education, 2026)
The study examines global research trends on the role of Extension Advisory Services (EAS) in advancing Climate-Smart Agriculture (CSA) from 1984 to 2024. Data retrieved from the Scopus database were analysed using VOS viewer and the R-based Bibliometrix package to map publication trends, citation influence, collaboration networks, and thematic evolution. The results show a sharp rise in research output after 2015, coinciding with global policy momentum following the FAO’s CSA framework and the Paris Agreement. Collaboration networks reveal strong linkages between African and European institutions, reflecting an emphasis on participatory and farmer-oriented approaches. Keyword and thematic analyses indicate a transition from conceptual discussions on extension and adaptation toward applied research focused on capacity building, innovation systems, and behavioural change. The findings highlight the critical role of EAS in enabling sustainable agricultural transformation. Strengthening institutional capacity, digital integration, and regional collaboration remains essential for enhancing the effectiveness of EAS in building climate resilience. Overall, EAS functions as the operational backbone of CSA by translating knowledge into adaptive, farm-level actions.